Legal Reconstruction: Ingsutan Paradigmatic on the Determination of the Positivism Paradigm and Legal Positivism in Law Enforcement in Indonesia - Unggul Basoeky (International Journal of Science and Society, 2019)
Law as control should regard the reality, values and factors that determine every society's behaviour or action. As defined by the positivism and legal positivism paradigm, law enforcement should shift into a constructivist legal paradigm framework to reconstruct a more comprehensive law. Written law has a limited reach because it is quickly left behind by considering that the text of statutory rules is formulated in a different space and time than the current conditions. Through hermeneutic interpretation of the law, law enforcers are expected to understand every legal issue confined in legal texts and the context of the reality of the problem in depth. Law enforcers are guided by the methodology of legal discovery, which is driven by applicable laws and human behaviour. Every person who carries out every behaviour or action (actus) must be understood to the deepest or hidden layer, namely the subjective motivations behind his actions. Law enforcers must view reality as conceptual reality by making ideas as hypotheses to understand truth collectively and comprehensively.